Inquisición, poder y escritura femenina en tiempos del conde-duque de Olivares (1621-1643): el caso de Teresa Valle de la Cerda - Muñoz Pérez, Laura S. (2013)
This thesis examines the importance of women in political and cultural life at the Spanish court through the case of Teresa Valle, spiritual counsellor of Olivares, the favourite of King Philip IV (1621–1643). Scholars have assumed that women in Golden Age Spain played only a minor role in high Baroque politics and culture; my research demonstrates this to be a partial and insufficient view. Through an analysis of diverse primary sources such as letters, literary writings, and Inquisition records I show how relations between noblemen and religious women formed a key aspect of Baroque patronage and exchange, forming an essential tool of publicity and power for the former, and a way of access to the literary domain for the latter. Teresa Valle founded a convent in Madrid with the help of her patrons. The fame as visionary achieved by her aroused the wrath of some of the nuns of her convent, who denounce her to the Holy Office. She was condemned and the enemy factions of her powerful friends used the scandal to destruct their public image. In order to defence her honour and the moral integrity of her patrons Teresa addressed three treatises to the inquisitors and one confessional writing to the King. At the heart of the thesis there is a study of the writings that Teresa produced during this period, revealing her emerging literary identity, which I tried to elucidate and analyse. The nun´s trip into literature also allows me to define new paths of understanding female writing in Golden Age Spain and clarify the discursive strategies that religious women negotiated.